Free trade and arms races: Some thoughts regarding EU-Russian trade - Rafael Reuveny; John W. Maxwell (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1998)
As NATO expands eastward, Russia has expressed growing concerns over what it sees as a threat to its national security. At the same time Russia is transitioning to a market economy, with the aim of becoming a free trade partner with the West. The question of concern to European nations is; how will Russia allocate the wealth it gains from freer trade with the west? Will the new found wealth make Russians feel more confident and secure, allowing for a reallocation of wealth towards consumption goods, or will the newly created wealth be allocated towards a new round of military build up? We examine these questions by modeling for the first time the effect of free trade between two potential political rivals, on their respective accumulation of weapons. Our model includes a rich setup in which utility maximization, the economics of trade and comparative advantage, production of weapons and consumption goods, depreciation of weapons stocks, technological spillover from production to national security, and the accumulation of capital are represented in an infinite horizon setting. The paper adopts a neoclassical two goods model of trade in which each actor specializes in producing the good of its comparative advantage and engages in trade. In the model, each country derives positive utility from consumption and its own stock of weapons. The impact of the foreign country`s weapons stock on the home country`s utility is negative (in the case of rivals). At each point in time, each actor chooses how to allocate its resources between the production of consumption goods and defense expenditures. Applying dynamic optimization, we find that whether free trade leads to a rise or a decline in each country`s stock of weapons relative to no trade depends on the relative marginal utilities of the consumption goods and weapons. The implications of these results to the trade and conflict debate are considered
Keywords: 330; Freihandel; Rüstungspolitik; Internationaler Wettbewerb; Außenwirtschaftstheorie; Zeitpräferenz; Theorie